Revealing teachers’ motivational strategies in Libyan English as a Foreign Language Classrooms - Azitoni, Remal (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, a positive consensus has emerged about how effective it is for teachers to use motivational strategies with formative learners of English as a foreign language. This study investigates its significance in Libyan primary public schools. The study employed a large scale empirical survey to collect the data. Seventy-six EFL teachers ranked a list of 48 motivational strategies on a Likert scale (1-6) from‘not important’ (1) to ‘very important’ (6). The quantitative results revealed that EFL teachers believed motivational strategies were highly relevant in motivating learners in the early stages of learning English as a foreign language. The four most important motivational clusters encompassed ‘proper’ teacher behaviour, encouraging learners’ self-confidence, recognizing students’ efforts and creating a productive and relaxed classroom climate. Less importance was attached to strategies related to increasing learners’ goal-orientedness, familiarising learners with second language (L2) values, promoting learners’ autonomy, and promoting group cohesiveness and group norms.